Understanding Country Differences : Predicting the Effect of Financial and Labor Market Conditions on International Doctoral Recipients’ First Labor Market Destination - Agbonlahor, Osasohan; Ampaw, Frim (Journal of International Students, 2021)
This study used the Survey of Earned Doctorates, World Bank economic data of the doctoral students’ home country, and hierarchical linear modeling analysis to examine the effects of financial factors and home-country macroeconomic indicators on international doctoral students’ labor market destinations. We found that wealth disparities and economic opportunities in the home country affect international doctoral student outcomes. Higher gross national income per capita was associated with a decreased likelihood of remaining in the United States, while higher unemployment rates in the home country significantly increased the likelihood of remaining in the United States. The study reveals a need to develop career services support for international doctoral students that are tailored to their needs as well as the need to internationalize the curriculum to support those who will eventually return to their home country.